ANALYSIS OF THE SPRUCE BUDWORM MODEL USING THE HEUN METHOD AND THIRD-ORDER RUNGE-KUTTA - Irwan, Irwan; Irwan, Muh; Rosmaniar, Rosmaniar; Alwi, Wahidah; Ibnas, Risnawati (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
This study discusses the analysis of the Spruce Budworm model using numerical methods, namely the Heun method and the Third Order Runge-Kutta method. The purpose of this study is to determine the numerical results of the Heun method and the Third Order Runge-Kutta method on the cypress caterpillar model and to determine the comparison of errors from the two methods, namely the Heun method and the Third Order Runge-Kutta method in analyzing the Spruce Budworm model. The results of the study using the Heun method for the initial conditions at years, for , the result obtained is and . For the calculation result of the Spruce Budworm model using the third-order Runge-Kutta method, the result obtained is and . while the error of Caterpillar Density with the third-order Runge-Kutta method is bigger than the Heun method, while the error of Branch Surface Area and the error of Reserve Food error using the Heun method bigger than using the third-order Runge-Kutta method.